Torsional thrust stand for characterization of microthrusters - Cheah, K. H. (2018)
This paper describes the setup of a precise thrust stand based on torsional pendulum design for characterizing the performance of microthrusters. Calibration has been carried out by using an improved version of electrostatic calibrator, which produces a wide range of accurate and repeatable calibration force. After the calibration, the thrust stand can resolve constant force from 40μN to 3.4mN and impulse bit from 7μNs to 340μNs. The usefulness of the thrust stand has been demonstrated by measuring the performance of two different microthrusters: a pulsed plasma thruster that produces impulse bit of 23.15μNs and a vaporizing liquid microthruster that produces steady state thrust of 633.5μN.